Solidaritas Sosial dalam Aktivitas Ekonomi Masyarakat Petani di Desa Baebunta Kecamatan Baebunta Kabupaten Luwu Utara - Putri, Sarah Arsitha; Bahri, Bahri (Jurnal Ekonomi dan Riset Pembangunan, 2023)
This research aims to answer: 1) Describing the Social Solidarity of Farmers in Baebunta Village, Baebunta Subdistrict, North Luwu Regency; 2) Factors that hinder and support the Social Solidarity of Farmers in Baebunta Village, Baebunta Subdistrict, North Luwu Regency. The purpose is to understand the solidarity of the farming community in Baebunta Village, Baebunta Subdistrict, North Luwu Regency, and to identify the inhibiting and supporting factors of social solidarity among the community in Baebunta Village, Baebunta Subdistrict, North Luwu Regency. The results of this study indicate that 1) The Social Solidarity of Farmers is characterized by high solidarity, politeness, mutual assistance, and helping others, which are common norms maintained within the community. 2) The uneven distribution of fertilizers among the community and the occurrence of modernization within the farming community.